New Insights into Different Reproductive Effort and Sexual Recruitment Contribution between Two Geographic Zostera marina L. Populations in Temperate China - Xu, Shaochun; Wang, Pengmei; Zhou, Yi; Zhang, Xiaomei; Gu, Ruiting; Liu, Xujia; Liu, Bingjian; Song, Xiaoyue; Xu, Shuai; Yue, Shidong (Frontiers in Plant Science, 2018)
Seagrasses are important components of global coastal ecosystems, and the eelgrass Zostera marina L. is widely distributed along the Atlantic and Pacific coasts in the temperate northern hemisphere, but limited datum related to the contribution of sexual reproduction to population recruitment have been reported. This study aimed to understand eelgrass sexual reproduction and population recruitment in Swan Lake (SLL), and Huiquan Bay (HQB) was included for comparison. Random sampling, permanent quadrats or cores and laboratory seed germination-based experimental methods were employed. The flowering, seed production, seed banks, seed germination, seedling survival and seedling growth of eelgrass were investigated from July 2014 to December 2015 to evaluate the contribution of sexual reproduction to population recruitment. Results indicated a dominant role of asexual reproduction in HQB, while sexual reproduction played a relatively important role in SLL. The highest flowering shoot density at center cite in SLL was 2.5 times greater than that of HQB, and SLL produced 1.8 times more seeds than HQB. The maximum sediment seed bank in SLL was 2.7 times greater than that in HQB. However, seeds in HQB were significantly larger and heavier than those in SLL (size: P = 0.004; weight: P < 0.001). Seeds in SLL were acclimated to spring germination (middle March–end May), while in HQB, they were acclimated to autumn germination (early October–late November). The recruitment from seedlings accounted for 41.36%-50.52% of the Z. marina population recruitment in SLL, while that accounted for as low as 2.53% in HQB. Our laboratory seed germination experiment showed that the seed germination percent in HQB was significantly greater than in SLL at optimal germination temperatures (10 and 15°C; P < 0.001). A laboratory seed germination test at suitable temperature may be a potential approach to identify the ecological differences among different geographic populations. It is suggested that the Z. marina population recruitment may have different strategies and acclimated to specific local conditions, such as in SLL and HQB, and the temperature regime may control morphological and phonological variations.